FRI0483-HPR Occupational characterization and relation between working condition and disease activity or functionality in patients with rheumatoid arthritis. (23rd January 2014) - Urbina, A.; Bello, J.M.; Cubides, M.; Amador, L.; Zambrano, D.; Villarreal, L.; Santos-Moreno, P.
Abstract : Background: Rheumatoid arthritis (RA) is a disease that in most cases is associated with disability and loss of earning capacity. There is a lack of information about occupation of rheumatoid arthritis patients in Colombia, being this field important in order to improve clinical and social outcomes for them. On the other hand, there are no data about the relationship between working or not-working condition with RA activity and functional status, being this information relevant for implementation of social programs for this population. Objectives: The aim of this study was to describe the occupation in a cohort of RA patients and to describe functionality and disease activity and its possible relationship with working or retirement condition in a cohort of RA patients in a specialized center in Colombia. Methods: A descriptive cross sectional study was realized. A revision of medical records of a cohort of RA patients was performed, including occupational therapy records. Each patient was evaluated for DAS28, HAQ and OPHI2 (Occupational Performance History Interview 2). Patients were classified in two categories: working and retirement condition, last one was divided into: retirement because of age and retirement for disability. Descriptive epidemiology was done, percentages and averages were calculated; and Pearson's statistics was used for by-variated analysis. Results: Of the 120 RA patients included, 21 (17.5%) were men and 99 (82.5%) women. Mean age 58.8 y/o, for women 58.3 and for men 61.2. Average DAS 28 for all patients 3.01, (3.07 for women and 2.73 for men), average HAQ were 0.36 (0.38 for women and 0.3 for men). Workers were 56 (46.6%), retired 64 (53.4%, because of age 40% and for disability 13.4%). Patient's occupations (percentage, DAS28 for workers, DAS28 for retired patients, HAQ for workers, HAQ for retired patients) were: cleaning services 24 (20%, 3.1, 2.6, 0.2, 0.45); administration 19 (15.8%, 3.0, 2.8, 0.4, 0.35); sewing operator 17 (14.2%, 3.1, 3.1, 0.6, 0.4); other operators 17 (14.2%, 3.3, 3.6, 0.35, 0.4); house keeper 13 (10.8%, 2.9, 2.2, 0.4, 0.25); maid services 11 (9.2%, 2.5, 3.0, 0.1, 0.4); kindergarten teacher 8 (6.7%, 3.9, 3.3, 0.3, 0.4); health worker 4 (3.3%, 3.2, 2.7, 0.1, 0.6); security 4 (3.3%, 3.1, 2.3, 0.37, 0.1) and floriculture 3 (2.5%, 3.8, 1.9, 0.1, 0.25). It was not established correlation between occupation and disease activity or functionality. Likewise it was not established correlation between working/retirement condition and disease activity or functionality. Conclusions: Interestingly most active RA patients were kindergarten teachers with an average moderate disease activity, followed by other operators and sewing operators. Less active disease scores were found on floriculture workers (maybe because they are all time in moving). In regard of functional status, sewing operators had higher scores followed by housekeepers; but in general for all types of occupations HAQ scores were low. Study suggests working patients had more active disease (average moderate activity) compared to retired patients (mild activity), but they had better functionality than retired patients. Disclosure of Interest: None Declared